KARAKTERISTIK TAFSIR PESANTREN: STUDI TAFSIR AL-BAYAN FI MA’RIFATI MA’ANI AL-QUR’AN KARYA KH. SHODIQ HAMZAH - Zulaikhah Fitri Nur Ngaisah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2023)
This article explains that Pesantren can present local interpretations typical of the archipelago through various Kiai, one of which is K.H Shodiq Hamzah whose style of arrangement is inseparable from the perspective of the thoughts of his predecessors. This article aims to describe the characteristics of the interpretation of Al Bayan fi Ma'rifatil Ma'ani Al-Qur'an by K.H Shodiq Hamzah, one of the works of interpretation of Indonesian scholars, which is still being studied in Pesantren. The method used in this research is descriptive qualitative with a centralized study approach. The results of this study are that the book of interpretation by K.H. Shodiq Hamzah is written using Pegon Javanese. The characteristics shown in this interpretation are; first, the al-Bayān interpretation text uses pego meaning, secondly, the presentation in this interpretation is thematically in verses of mushafi tartib